An ultrastable lithium metal anode enabled by designed metal fluoride spansules - Yuan, Huadong (2020)
The lithium metal anode (LMA) is considered as a promising star for next-generation high-energy density batteries but is still hampered by the severe growth of uncontrollable lithium dendrites. Here, we design “spansules” made of NaMg(Mn)F3@C core@shell microstructures as the matrix for the LMA, which can offer a long-lasting release of functional ions into the electrolyte. By the assistance of cryogenic transmission electron microscopy, we reveal that an in situ–formed metal layer and a unique LiF-involved bilayer structure on the Li/electrolyte interface would be beneficial for effectively suppressing the growth of lithium dendrites. As a result, the spansule-modified anode affords a high Coulombic efficiency of 98% for over 1000 cycles at a current density of 2 mA cm−2, which is the most stable LMA reported so far. When coupling this anode with the Li[Ni0.8Co0.1Mn0.1]O2 cathode, the practical full cell further exhibits highly improved capacity retention after 500 cycles.